Spontaneous re-eruption, surgical or orthodontic extrusion: What is the choice for intrusive luxation in permanent teeth? - Costa, Luciana Artioli [UNESP]; Ribeiro, C. C. [UNESP]; Cantanhede, L. M. [UNESP]; Santiago Júnior, J. F. [UNESP]; De Mendonça, M. R. [UNESP]; Pereira, A. L. [UNESP] (Elsevier, 2017)
Data sources Medline, Embase, the US Clinical Trials and ISRCTN Registry databases. Study selection Two reviewers independently selected studies. Interventional and observational studies comparing the outcomes of orthodontic or surgical re-position of intrusive luxation of permanent teeth compared with spontaneous re-eruption were considered. Data extraction and synthesis Two reviewers abstracted data and assessed study quality using the Cochrane Risk of Bias tool. Periodontal and pulpal outcomes after treatment were compared using risk ratios (RR) with 95% confidence intervals (CI) and meta-analysis conducted. Results Eight studies involving a total of 440 patients were included. All of the studies were considered to be at high risk of bias. A meta-analysis of four studies comparing surgical re-positioning vs spontaneous re-eruption suggested no significant difference RR = 1.30 (95% CI; 0.90-1.88) P = 0.16. Meta-analyses were also performed for secondary outcomes and other sub-groups. Conclusions While the review suggests that spontaneous re-eruption should be the treatment of choice the quality of the available evidence is poor.